The Role of the "Kachar" Scientific Center in the Advancement of Armenian Studies in Artsakh - Harutyunyan, Mher; Avanesov , Hovik (History and Culture, 2025)
After the declaration of independence, significant progress was made in the Republic of Artsakh in the fields of state-building, as well as in spiritual, cultural, and scientific-educational spheres. To support these processes, the "Kachar" Scientific Center was established in 2006 in Shushi, which played a significant role, particularly in the development of Armenian Studies and the research of Artsakh's history. The professional library and archive of Artsakh's history housed unique materials on the Artsakh Movement, the national liberation war of 1991-1994, and the periodical press published in Artsakh.In order to address current issues in Armenian Studies and introduce unpublished documents into the scientific discourse, the Center published the "Kachar Bulletin" and later the Yearbook, along with methodological works, collections of documents, and studies on the history of journalism in Artsakh. In 2008, in collaboration with the Shusha History Museum, the Center conducted research on newly discovered monuments. In 2011, the Center successfully implemented a grant project aimed at the development of Armenian Studies, engaging young specialists in the field.A key area of the Center's activity was the organization of international scientific conferences on strategically important topics and the publication of conference materials, which provided a significant boost to the development of Armenian Studies in Artsakh.In November 2020, Shusha was captured, resulting in the loss of an important part of the intellectual heritage of the Armenian people, which had been carefully collected and preserved at the Center. However, public initiatives to develop the Artsakh school of Armenian Studies continued in Stepanakert, and in 2023, after the complete occupation of Artsakh, the Center moved to Yerevan, where it continues its Armenian Studies research.The Center's publications have been digitized and are available on the website of the National Library of Armenia.
Keywords: Artsakh; Shushi; Kachar; Armenian Studies; Culture; Intellectual heritage; Archive; Yearbook; Publishing House; Scientific Conference